PENGEMBANGAN MANAJERIAL DALAM MENGHADAPI MASYARAKAT EKONOM DI KELOMPOK LPK DESA SUNGAI PUTIH, KECAMATAN TAPUNG KABUPATEN KAMPAR - Azmi, Fauzan; Irawan, Dika; Hidayat, Novit; Primadayani, Syurti; Nurhayati , Nurhayati (Jurnal Pengabdian Kompetitif, 2024)
This training and managerial development was carried out in Sungai Putih village, Tapung sub-district, Kampar regency. At this training event, material and skills that were important in facing the challenges of the world of work were presented. Participants were encouraged to recognize and apply the techniques and methods that they must have in order to be able to win the competition in in the world of work and business, in good management, before carrying out an activity or business, business actors must master the most basic things in achieving goals such as careful planning, good organization, implementation in accordance with planning up to the evaluation stage in each division. Thus, this training provides significant benefits for participants both in increasing their knowledge about good managerial management and improving their skills in dealing with complex problems in the world of work. Participants are expected to be able to apply the knowledge they have acquired in an effort to achieve work that suits their abilities and abilities. skills possessed.Keywords: Training, managerial, economic society